The Silent Band: Laparoscopic Adjustable Gastric Band Erosion as an Incidental Finding During Endoscopy - Lefika Bathobakae MD, MPH; Tiffany Varadi BS; Rammy Bashir MD, MSc; Atang Koodirile BS; Ruhin Yuridullah MD; Kamal Amer MD; Yana Cavanagh MD (SAGE Publishing, 2024)
Laparoscopic adjustable gastric banding (LAGB) is a bariatric procedure that was introduced in the early 1990s and offers a minimally invasive and reversible option for weight loss. Initially popular due to its simplicity and effectiveness, LAGB's long-term success has been limited by complications such as port-site infection, pouch dilatation, and gastric band erosion. Herein, we describe a rare case of gastric band erosion found incidentally during endoscopy a decade after placement. The eroded band was successfully removed using a combined endoscopic and laparoscopic approach.